MANAGING DISRUPTIVE BEHAVIOUR OF PRIMARY STUDENTS IN THE EFL CONTEXT (Mengatasi Perilaku Mengganggu yang Dilakukan oleh Siswa Sekolah Dasar dalam Konteks Pembelajaran Bahasa Inggris) - Azizah, Umu Arifatul; Rejeki, Sri; Prihandoko, Lastika Ary (Balai Bahasa Kalimantan Tengah, 2018)
Not all students are well motivated in the classroom activities. Some students often show disruptive behaviors that influence the teacher in conducting learning process. In particular case, there is special issue regarding behavioral problems in elementary school such as talking without permission and disturbing other friends while studying in class. Accordingly, this study aims at discerning behavior interruptions found in English teaching class. Moreover, it also describes the classification of students? disruptive behaviors and explores teachers? actions in order to overcome those behaviors. In this research, depth-interview with the English teacher, classroom observation and documentation were used to collect the data for two perceived classes and interactive model was used to analyze the data. Each class has been chosen based on specific characteristics for being observed. Though the study reported that there were several disruptive behaviors exhibited by primary school students, it could be classified as non-violence behavior since no one was injured by physical force. It seems possibly categorized as normal behavior by considering the students? age and level in school. In the EFL context, students will be more focus and motivated if they are studying in comfortable class because students are required to master several skills of English. Comfortable class will lead them to comfortable learning. Henceforth, it was suggested that teacher should have adequate knowledge of the students? psychology based on their age in order to give the proper strategies to control disruptive behaviors in the classroom.